Primary mesodermal dysgenesis of the cornea (Peter´s anomaly) (Ukrainian Journal of Ophthalmology, 2025)
Primary mesodermal dysgenesis of the cornea, also known as Peter´s anomaly (PA) or keratolenticular dysgenesis, is a rare congenital eye condition caused by an abnormal development of the anterior segment. PA is characterized by unilateral or bilateral corneal opacity (leucoma), that appears since the early neonatal period. The incidence of PA in the United States of America is approximately 1.5 per 100,000 live births. PA is known as Peters-plus syndrome when it presents with systemic malformations. In this article we describe the clinical presentation of an 18-year-old patient with PA that arrived to medical consultation due to bilateral corneal opacities since birth. The patient´s parents refer that he has hypoacusis and deny other systemic pathologies. Clinical exploration reveals a visual acuity of 20/30 of the right eye and 20/100 of the left eye. According to the clinical findings and the absence of systemic anomalies, the patient was diagnosed with PA type II.
Keywords: сongenital; Peter´s аnomaly; leucoma; cataract